Pattern and Determinants of Self-Reported Lower Limb Pain Among Libyan Female Teachers in Elementary Schools of Tripoli, Libya - Aisha Benrween; Shaban Eshakshouki; Sana Ashur; Fatma Ibrahium (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. School teachers represent an important work group. Lower limb pain is a common work-related problem among teachers, though its magnitude and pattern were not explored in Libyan school settings. This study described the prevalence and pattern of self-reported lower limb pain among Libyan female school teachers. The study also examined the association between the self-reported lower limb pain and selected demographic, medical and work-related factors. Methodology: A cross sectional study was conducted among female school teachers in the western district of Tripoli. Data analysis was performed using the SPSS version 6. Results. A total of 241 female school teachers participated in the study, their mean age was 40.5 (SD=8.5) years. The prevalence of lower limb pain was 80.1%. In the majority of those who reported lower limb pain, the pain was a bilateral legs pain (81.3%), and in about half of them was provoked by prolonged standing (51.3%). Out of all studied variables, the bivariate analysis showed a statistically significant association between the self-reported lower limb pain and the presence of chronic disease (p=0.011). The contribution of having a chronic disease to reporting lower limb pain persists in the multivariate analysis (OR=9.647, 95% CI= 1. 279-72.784), though, this should be cautiously interpreted because of the wide confidence interval of the odds ratio. Conclusion. Lower limb pain is a considerable problem among female school teachers in Libya. Programs directed to increase awareness among teachers about the impacts of static standing and to promote practicing dynamic standing are recommended.